1989
DOI: 10.1007/bf00253598
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoscintigraphy of ovarian cancer with 131-iodine labeled OC-125 antibody fragments

Abstract: Radioimmunoscintigraphy (RIS) with 131I labeled OC-125 F(ab')2 monoclonal antibody fragments was prospectively studied in 43 women for primary diagnosis and follow up of ovarian cancer. Total body planar photoscans with a scintillation camera were performed one to seven days after antibody application and results were compared with operation and or CT examination. By the region of interest technique the tumor to non tumor tissue ratio (T/N) was calculated in vivo. Sensitivity in primary diagnosis was 100% (10/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…of patients 13-45) for different kinds of adenocarcinomatous lesions [4,9,16,20,24,25]. The high value of 96.6% for locoregional specificity confirms the results of a pilot clinical trial using 99mTc-MAb-170 that showed no false-positive result in six patients with cancer of the ovary or the fallopian tube [15].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…of patients 13-45) for different kinds of adenocarcinomatous lesions [4,9,16,20,24,25]. The high value of 96.6% for locoregional specificity confirms the results of a pilot clinical trial using 99mTc-MAb-170 that showed no false-positive result in six patients with cancer of the ovary or the fallopian tube [15].…”
Section: Discussionsupporting
confidence: 72%
“…of patients: 10-45). These findings appear to indicate that radioimmunoscintigraphy with 99mTc-MAb-170 represents a reliable diagnostic tool in cases of ovarian carcinoma [2,6,7,13,[15][16][17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 98%
“…Barzen et al [37] (in a study utilizing 1311-labelled OC 125), reported a sensitivity of 100% and a specificity of 33% in the primary detection of ovarian cancer. In detect ing a recurrent ovarian cancer, the specificity of radionu clide imaging increases.…”
Section: Radionuclide Imagingmentioning
confidence: 99%
“…The aim of the present study was to test intratumoral injection of a 9oY-labeled tumor-nonspecific antibody in a nude mouse model. We selected OC 125 (8) as antibody for this model, since it has been clinically used under various auspices (9)(10)(11)(12)(13) and also carefully studied in mouse K . KAIREMO ET AL.…”
mentioning
confidence: 99%